ANALISIS STABILITAS LERENG PADA BADAN JALAN DAN PERENCANAAN PERKUATAN DINDING PENAHAN TANAH - Suwarsa Putra, Tjokorda Gde; Wirya Ardana, Made Dodiek; Aryati, Made (Jurnal Ilmiah Teknik Sipil; Vol. 14, No. 1 Januari 2010)
The stability of the slope, a soil surface that forms an angle to the horizontal plane, on the road in the Bantas village, East Selemadeg District, Tabanan Regency is discusses in this paper. The road which connects the city of Denpasar-Gilimanuk is always packed with traffic flow. Landslides that occurred during the rainy season in January 2006 caused long traffic jams, the changes in the contour slopes and the possibility for landslide aftershocks. Slope stability analysis is conduced on naturally slope contour and that with the traffic loading. The analysis was carried out using the simplified Bishop’s Method by dividing the slope into three parts according to soil type and location of its coordinates. Based on the results conducted on slope stability analysis for type 1 soil both at the bottom and at the top of the road, the average safety factor of slope stability was less than 1. To prevent the occurrence of landslides, it was planned an alternative form of construction namely cantilever retaining walls with reinforced concrete at the bottom of the road and gravity retaining walls with stone at the top of the road until reaching a stable rate (Fs > 1.5). The results obtained for the upper slopes of the road built with 1.5 meters retaining walls of gravity type (with ribs) are number of safety of overturning and shear stability which is greater than 1.5 and the actual bearing capacity which is smaller than its allowable bearing capacity. Likewise for the slope at the bottom of the road after the 8 meters cantilever wall was built, the results obtained meet the safety requirements.
Keywords: slope stability, safety factor, retaining wall, landslide